Encyclopedia of Social Work in India Volume II - Planning Commission (Planning Commission, 1968)
Minimum standards for social welfare services can be defined as those basic commonly accepted norms which the services must observe, in all areas of their work, if the very purposes for which the services stand are to be fulfilled. According to a dictionary, a standard is a basis of measurement, a criteria, an established or accepted model. the term “Standard” therefore, connotes general acceptance and, implicitly, a need for enforcement.
Planning Commission Government of India
Planning Commission Government of India